Influence of aging environment on low-temperature degradation of tetragonal zirconia alloys - Kim, DJ (ELSEVIER SCI LTD, 1997)
Y2O3-stabilized tetragonal zirconias, alloyed with Ta2O5 and Nb2O5, were annealed at 100-265 degrees C in air, dry air, and vacuum to elucidate the role of moisture in the low-temperature degradation (LTD). Although the existence of moisture enhanced the extent of LTD in accordance with observations in the literature, the influence of H2O on the extent of the degradation became less significant as the residual stress in 3Y-TZP was enhanced by the Nb2O5 alloying and with increase in the gl ain size. This suggested that a residual stress is accumulated on the specimen surface during low-temperature aging, which probably originates from diffusion of oxygen vacancies from the specimen surface into the interior. This rationalization was based on the observation that LTD is an isothermal process and the activation enthalpy for LTD is similar to that for the diffusion of oxygen vacancies in the Y2O3-stabilized tetragonal zirconia at low temperatures. (C) 1997 Elsevier Science Limited.
Keywords: PARTIALLY-STABILIZED ZIRCONIA; TRANSFORMATION; YTTRIA; POLYCRYSTALS; ZRO2; Y2O3; WATER; NB2O5; CEO2; AIR